Human papillomavirus (HPV) as the causal factor of tympanal cholesteatoma in malignant-type chronic suppurative otitis media - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Background: Tympanal cholesteatoma is an uncoordinated, uncontrolled hyperproliferative epidermic epithelial cells keratinized with aggressive, erosive and destructive development to the mucous membrane and the bone of external auditory canal and tympanic cavity. This process is invasive and may migrate to the surrounding tissue. Ethiopathogenesis of tympanic cholesteatoma is unknown. Histological examination shows that there are hyperproliferative development, papillomatous, koilocyte clusters and destruction of the bone. These abnormalities are characteristics of papillomavirus. Objective: To know the whether HPV-18 is the risk factor in the occurrence of tympanic cholesteatoma ini malignant-type chronic suupurative otitis media. Methods: A case-control study was conducted on 31 tympanal cholesteatoma specimens from malignanttype chronic suppurative otitis media as the case group, and 31 mucosal tympanic cavity specimens from benign-type chronic suppurative otitis media as the control group. For detecting Polymerase chain reaction (PCR) examination was used to detect DNA HPV-18, that performed in Parasitology laboratorium Faculty of Medicine, Gadjah Mada University. Results: Polymerase chain reaction (PCR) examination showed that there were 21 (67.7%) DNA HPV-18 positive specimens in the case group, while in the control group there were 5 (16.1 %) DNA HPV-18 positive specimens. This difference was statistically significant (p = 0.0001